2019
DOI: 10.3390/biom9080351
|View full text |Cite
|
Sign up to set email alerts
|

E6 Oncoproteins from High-Risk Human Papillomavirus Induce Mitochondrial Metabolism in a Head and Neck Squamous Cell Carcinoma Model

Abstract: Head and neck squamous cell carcinoma (HNSCC) cells that are positive for human papillomavirus (HPV+) favor mitochondrial metabolism rather than glucose metabolism. However, the involvement of mitochondrial metabolism in HNSCC HPV+ cells is still unknown. The aim of this work was to evaluate the role of E6 oncoproteins from HPV16 and HPV18 in the mitochondrial metabolism in an HNSCC model. We found that E6 from both viral types abates the phosphorylation of protein kinase B-serine 473 (pAkt), which is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 67 publications
1
25
1
Order By: Relevance
“…None of these genes were associated with altered survival in HPV-HNSCC, reinforcing the concept that HPV+ and HPV-HNSCC are distinct tumour entities [7][8][9]23]. This is not unexpected, as E6 from HPV16 and HPV18 can increase the expression of mitochondrial cellular respiration genes in a head and neck cancer cell line [24], which matches our observation of increased expression of these genes in HPV+ HNSCCs when compared to HPV-HNSCCs. In addition, E6 and E7 may also be responsible for perturbing glycolysis in HPV+ cervical cancer cells [25,26], which could explain our observation of increased expression of glycolytic genes in HPV+ HNSCC as compared to normal control tissues.…”
Section: Discussionsupporting
confidence: 88%
“…None of these genes were associated with altered survival in HPV-HNSCC, reinforcing the concept that HPV+ and HPV-HNSCC are distinct tumour entities [7][8][9]23]. This is not unexpected, as E6 from HPV16 and HPV18 can increase the expression of mitochondrial cellular respiration genes in a head and neck cancer cell line [24], which matches our observation of increased expression of these genes in HPV+ HNSCCs when compared to HPV-HNSCCs. In addition, E6 and E7 may also be responsible for perturbing glycolysis in HPV+ cervical cancer cells [25,26], which could explain our observation of increased expression of glycolytic genes in HPV+ HNSCC as compared to normal control tissues.…”
Section: Discussionsupporting
confidence: 88%
“…It has previously been described that high-risk alphaHPV early proteins interact with mitochondria 19 . Most recently it has further been demonstrated, that the E6 protein of high-risk alphaHPVs induces the mitochondrial metabolism by increasing the protein levels of various mitochondrial complexes 20 . Here, we now show that E7 of HPV8, HPV11 and HPV16 all interact with varying affinity with the mitochondrial ATP synthase subunit ATP5B, which may therefore represent a conserved interaction across alpha and beta HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Cruz-Gregorio et al recently showed that HPV16 increases protein levels of subunits of mitochondrial complex I-IV as well as the ATP synthase, leading to increased mitochondrial mass. Furthermore, E6 thus increases basal and leak respiration, which was associated with oxidative stress by increasing the amount of reactive oxygen species without having an effect on ATP-linked mitochondrial activity 20 . From these results the authors concluded that this may partially explain why HPV positive OPSCC are more radiosensitive due to oxidative stress and the resulting DNA damage and the susceptibility to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…The latter increases mitochondrial metabolism; however, ROS levels also augment, producing OS and DNA damage. 72 In cervical cancer, HR-HPV16 E7 activates Akt to induce pirin protein. Pirin activates nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) to protect against OS.…”
Section: The Akt/tsc2/mtorc1 Pathway Regulated By Hr-hpv Proteinsmentioning
confidence: 99%
“…HR-HPV proteins can bind and modify the different functions of mitochondria and the signalling pathways associated with the functioning of these organelles. 1,72 For instance, it showed that in HPV negative cervical cancer cells, HR-HPV16 E6* induce SOD2 and GPX 1/2 overexpression, OS and DNA damage.…”
Section: Hr-hpv and Mitochondrial Pathwaysmentioning
confidence: 99%